Factors Affecting the Physician's Disclosure of Truth to Cancer Patients in Iran - Aghili, Mahdi; Yamrali, Maisa; Akbari, Razieh; Kazemian, Ali (Archives of Breast Cancer, 2017)
Background: One of the essential issues in doctor-patient relationship is the matter of telling the truth of cancer diagnosis to patients. This is not only important from an ethical standpoint, but also can have legal implications. Thus, truth-telling and its associated factors are of great importance especially in cancer patients. The aim of this study was to evaluate factors effective in doctors’ telling the truth to their patients. Methods: The statistical population included specialists and subspecialists working in the field of cancer treatment in Tehran. Overall, 161 questionnaires, designed for our study, were gathered and evaluated. Results: According to our study, 87.6% of the responders would tell the truth to their patients, while 12.4% wouldn't do so. They believed that the best person to tell the truth to the patient is the physician or the psychiatrist specialized in this field. Ninety-two percent of physicians felt the need for developing a guideline on educating patients. There was a significant difference between oncologists and non-oncologists in terms of tendency to tell the truth, with non-oncologists showing more tendency. Most of the doctors preferred to tell the truth to their middle-aged (51–70 years) patients rather than to their younger or older patients. Conclusion: Only 25.5% of physicians in our study had the policy to tell the truth to the majority of their patients, and almost all of them felt the need for having a formal guideline regarding informing and educating cancer patients. This highlights the significance of cultural-religious context of our country and the importance of having a practical guideline to educate our physicians.